Midterm Outcome of Open Wedge High Tibial Osteotomy without Bone Graft with Locking Plate Fixation - Sungkhun, MD, Pawaris (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: The purpose of this study was to assess the midterm outcomes of open-wedge high tibial osteotomy without bone graft (OWHTO) in patients with advanced medial compartment arthritis. Methods: From January 2014 to December 2020, all patients treated with OWHTO had medial compartmental arthritis. Twenty patients underwent OWHTO. Clinically, we evaluated the Oxford Knee Score (OKS), Knee Society Score (KSS), and range of motion (ROM) at the five years follow-up. Results: The mean age of the patients was 52.65±4.88 years. All clinical outcomes gradually improved from the postoperative period to the final follow-up period. The mean follow-up duration was 5.05±0.43 years. Pre-operative OKS was 20.85±3.47; Post-operative OKS was 36.70±2.16; P = 0.034. Pre-operative KSS was 35.8±20, Post-operative KSS was 53.2±20.2, and P = 0.02. Pre-operative ROM was 100.59±11.22; Post-operative ROM was 120.57±11.06; P = 0.044. Conclusions: OWHTO has good clinical outcomes. Thus, the results of this study suggest that OWHTO may be a good alternative treatment for medial unicompartmental arthritis.